Analisis Faktor Penyebab Gangguan Pencernaan pada Remaja di Lingkungan Sekolah SMP IT Mutiara Aulia - Amraina Simamora; Nazwa Nuha NST; Rahmi Zahara; Susi Andani; Melisa Andriani; AlHilalwi Anwar Tanjung; Elvi Zuliani (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
This study aims to describe dietary patterns, food consumption habits, hygiene awareness, and environmental and social factors related to digestive disorders in junior high school students. This study used a descriptive approach with a closed-ended interview method (Yes/No answers) with Thirty-five junior high school students using 15 questions. The results showed that some students did not have consistent breakfast habits, had a high tendency to consume fried foods and sugary drinks, and demonstrated low awareness of food safety and hygiene habits such as washing hands before eating. In addition, the school environment, peer influence, and psychological well-being influence students’ eating patterns. These factors contribute to digestive problems in some students. Therefore, schools must actively participate in maintaining a clean environment, providing students with healthy food options, and providing ongoing nutritional instruction on digestive health.